2019
DOI: 10.1089/tmj.2018.0049
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Assessment Via Telepractice Is Comparable to Face-to-Face Assessment in Children with Reading Difficulties Living in Rural Australia

Abstract: Web-based technology can enable remote delivery of literacy assessments. The technology has the potential to increase the availability of assessments to meet the needs of children who live remotely, in a timely manner and at their family's convenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 7 publications
0
62
0
Order By: Relevance
“…Two studies used surveys (Hodge et al 2019, Vasquez andSlocum 2012), one recorded qualitative observations of student engagement during telepractice sessions (Houge and Geier 2009) and one used informal conversation (Wright et al 2011). Together, these four studies suggest that students were engaged in their telepractice sessions (Hodge et al 2019) and wanted to attend. They reportedly showed an increased interest in reading following telepractice instruction (Houge and Geier 2009).…”
Section: Outcome Measuresmentioning
confidence: 94%
See 4 more Smart Citations
“…Two studies used surveys (Hodge et al 2019, Vasquez andSlocum 2012), one recorded qualitative observations of student engagement during telepractice sessions (Houge and Geier 2009) and one used informal conversation (Wright et al 2011). Together, these four studies suggest that students were engaged in their telepractice sessions (Hodge et al 2019) and wanted to attend. They reportedly showed an increased interest in reading following telepractice instruction (Houge and Geier 2009).…”
Section: Outcome Measuresmentioning
confidence: 94%
“…For the two studies evaluating the use of telepractice for administration of reading and spelling assessments, results revealed a high level of agreement between onsite and online scoring of assessments by administrators (Hodge et al 2019, Waite et al 2010. For Hodge Lisa Furlong et al et al (2019), results showed very strong agreement between telepractice and onsite scores across all but one assessment, which still demonstrated strong agreement (Hodge et al 2019). For Waite et al (2010), scores obtained from the onsite and online environments were not significantly different indicating that the testing environment did not affect the accuracy of the online assessment (Waite et al 2010).…”
Section: Telepractice Reading and Spelling Assessmentmentioning
confidence: 96%
See 3 more Smart Citations